PENGARUH PENGALAMAN KERJA, INDEPENDENSI, OBJEKTIVITAS DAN MOTIVASI TERHADAP KUALITAS HASIL PEMERIKSAAN APIP DILINGKUNGAN INSPEKTORAT KABUPATEN AGAM - Ratna Dewi (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of the research is to find out the influence of Work Experience, Objectivity, Independence, Motivation to the Quality of Examination Results, so that APIP Capability Improvement can realize effective Governance clean, accountable and serving. This type of research is qualitative research, the data comes from several things, namely in the form of words and actions. The rest is additional data such as documents and others. This research includes associative research. The population in this study is 59 APIP working in the Inspectorate of Agam Regency. The study used a used trial with 41 respondents used to test this research instrument taken from within the population. The prerequisite test of analysis includes linearity test, heterochemicity test, and multicollinearity test. The data analysis techniques used are simple linear regression analysis, multiple linear regression, and Moderated Regression Analysis. The observations submitted by the author use the questionnaire method with all APIPs working in the Agam Regency Inspectorate. The results of this study show that (1) Work Experience affects the Quality of Examination results. This is indicated by a coefficient of determination of 0.136 which means that work experience affects the quality of examination results by 13.6%. (2) Competence affects the Quality of examination results. Competence affects the quality of the examination results. This is indicated by a coefficient of determination of 0.110 which means that objectivity affects the quality of the examination results by 11%. (3) Independence affects the Quality of examination results. This is indicated by a coefficient of determination of 0.160 which means that Independence affects the Quality of examination results by 16%. (4) Work Experience, Objectivity, and Independence simultaneously affect the Quality of examination results. This is indicated by a coefficient of determination of 0.258 which means that Work Experience, Objectivity, and Independence simultaneously affect the Quality of examination results by 25.8%. (5) Work Experience, Objectivity, Independence and Motivation affect the Quality of examination results with Motivation as a moderating variable. This is indicated by a coefficient of determination of 0.277 which means that Work Experience, Objectivity, Independence and Motivation affect the Quality of examination results by 27.7%.